(untitled) (Applied Biological Research, 2015)
The leaves, tubers and other morpho-culinary characters of nine taro [Colocasia esculenta var. antiquirom (L) Schott.] cultivars were considered for development of distinct, uniform and stable (DUS) standards using digital morphometrics and computational methods besides taking help from prototypes of hand-held digital field guides and various robotic systems to bring them under IPR-related regimes. Out of 48 morpho culinary characters studied maximum were polymorphic in nature. Some cultivars possessed unique stable characters helpful for their identification. The study revealed that DUS descriptors using digital morphometrics can be used effectively for identification and grouping of taro germplasm.